2013
DOI: 10.1183/09031936.00186212
|View full text |Cite
|
Sign up to set email alerts
|

Slow-growing lung cancer as an emerging entity: from screening to clinical management

Abstract: The current paradigm is that untreated lung cancer is invariably and rapidly fatal, therefore the medical community normally dismisses the idea that a patient could live with such a disease for years without any therapy.Yet evidence from lung cancer screening research and from recent clinical series suggests that, although rarely recognised in routine practice, slow-growing lung cancers do exist and are more common than previously thought.Here, current evidence is reviewed and clinical cases are illustrated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 155 publications
1
34
0
1
Order By: Relevance
“…The tumour stage, VDT, patient's history and preferences will all determine the extent of the resection and the procedure chosen [56]. Table 5 summarises the lung cancer screening-related (both diagnostic and definitive procedures) complications and mortality rate as reported by the major trials.…”
Section: Procedural Complications Of Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumour stage, VDT, patient's history and preferences will all determine the extent of the resection and the procedure chosen [56]. Table 5 summarises the lung cancer screening-related (both diagnostic and definitive procedures) complications and mortality rate as reported by the major trials.…”
Section: Procedural Complications Of Screeningmentioning
confidence: 99%
“…al. [56], and the corresponding editorial by REVEL [57], the slow-growing lung cancer is extensively discussed. A high VDT value of more than 400 days is one of the methods used to …”
Section: Screening Biasesmentioning
confidence: 99%
“…It is well accepted that overdiagnosis is an issue for cancer screening programs and that CT screening identifies many lung cancers that may not be life-threatening (8)(9)(10)(11)(12)(13)26). In an analysis of the NLST study, it was estimated that overdiagnosis accounted for about 18.5% of all lung cancers detected in the CT arm (8).…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer this has been arbitrarily defined as greater than 365-400 days (10)(11)(12). Applying this criterion to the results from a single-arm CT screening trial of 3,642 smokers, Wilson and colleagues reported that 48% of non-small cell lung cancer cases, and 67% of prevalent cancers, were slow growing and potentially defined as overdiagnosed cancers (11).…”
mentioning
confidence: 99%
“…Tumor doubling time has been proposed as a marker for malignancy [8][9][10], and the current standard for measuring tumor response, Response Evaluation Criteria in Solid Tumors (RECIST) [11], is based on uni-dimensional, linear measurements of tumor diameter. Measurements are made manually, and significant inter-observer variability exists [12][13][14].…”
Section: Introductionmentioning
confidence: 99%